Effect of Nanomaterials on the Mechanical and Morphological Properties of Jute-GFRP Hybrid Nanocomposites - Rabbi, Sanaul; Das, Snigdha; Sharmin, Sanjida; Al Mamun, Abdullah (Malaysian Journal on Composites Science and Manufacturing, 2024)
Nanocomposites have garnered significant attention both within the realms of science and industry over the past decade due to their exceptional attributes, such as improved mechanical and thermal properties, gas permeability resistance, optical clarity, electrical conductivity, magnetic responsiveness, and flame-retardant characteristics. This study comprehensively investigates the influence of nano Al2O3, ZnO, and TiO2 on the mechanical and morphological traits of jute-glass fiber reinforced plastic (GFRP) hybrid composites. Employing a deliberate inclusion of 3% weight of each respective nano filler, the research scrutinizes the tensile and flexural strengths of the hybrid nanocomposites. The fabrication of specimens was accomplished through the hand lay-up method, ensuring precision and consistency. The structural integrity and failure mechanisms of the composite specimens were meticulously examined through the utilization of Field Emission Scanning Electron Microscopy (FE-SEM). The FE-SEM images vividly depict intricate details, showcasing discernible features such as fiber pull-outs, breakages, voids, and internal cracks on the fractured surfaces. The tensile strength of the hybrid nanocomposites has been higher at 3% nano ZnO addition, and flexural strength has been higher at 3% nano TiO2.